Synthesis, Antibacterial and Antifungal Activities of New Bis-5(6)-nitrobenzimidazoles - Kucukbay, Hasan; Durmaz, Riza; Sireci, Nihat; Gunal, Selami (Asian Journal of Chemistry, 2010)
Seventeen bis-5(6)-nitrobenzimidazole compounds and their salt derivatives were synthesized from the reaction of 5(6)-nitrobenzimidazole and appropriate alkyl dihalides and alkyl halides. The synthesized compounds were identified by 1H, 13C NMR, FT-IR spectroscopic techniques and elemental analysis. All compounds studied in this work were screened for their in vitro antimicrobial activitiy against the standard strains such as Staphylococcus aureus ATCC 29213, Enterococcus faecalis ATCC 29212, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853 and the yeasts Candida albicans and Candida tropicalis. Ten of the compounds were found effective to inhibit the growth of gram positive (E. faecalis and S. aureus) at MIC values between 50-400 μg/mL. Seven of the compounds exhibit antimicrobial activity against gram negative bactreria (E. coli and P. aeruginosa) at the concentrations studied (50-400 μg/ mL). Nearly all compounds tested in this work showed antifungal activity with a range of the MICs between 50 and 800 μg/mL.